2016
DOI: 10.1542/neo.17-9-e554
|View full text |Cite
|
Sign up to set email alerts
|

Recomendaciones terapéuticas del VII Consenso Clínico de SIBEN para la encefalopatía hipóxico-isquémica neonatal

Abstract: Starting with this issue of NeoReviews, the editorial board has decided to publish a few articles in Spanish every year and make them available online for free. To accomplish this, NeoReviews came to an agreement with SIBEN, the Ibero-American Society of Neonatology, to publish Clinical Consensus statements that the Society works very hard to produce. This collaborative process involves more than 40 neonatologists and neonatal nurses from 12 to 14 countries of the Ibero-American region, who work in various sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 73 publications
0
1
0
2
Order By: Relevance
“…In the first decade of this century, meta-analyses of clinical trials showed that TH, reducing brain temperature by 3-4 C through cooling of the whole body or the head, is a safe and effective intervention to reduce the mortality and disability associated with HIE (Edwards et al, 2010;Jacobs et al, 2007;Shah, 2010;Tagin et al, 2012). Since 2005, TH has been progressively introduced into neonatal units worldwide to become established as the standard treatment for moderateto-severe HIE in the newborn (Azzopardi, 2010;Blanco et al, 2011;Lemus-varela et al, 2016;NICE Interventional Procedure Guidance [IPG347], 2010;Peliowski-Davidovich et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In the first decade of this century, meta-analyses of clinical trials showed that TH, reducing brain temperature by 3-4 C through cooling of the whole body or the head, is a safe and effective intervention to reduce the mortality and disability associated with HIE (Edwards et al, 2010;Jacobs et al, 2007;Shah, 2010;Tagin et al, 2012). Since 2005, TH has been progressively introduced into neonatal units worldwide to become established as the standard treatment for moderateto-severe HIE in the newborn (Azzopardi, 2010;Blanco et al, 2011;Lemus-varela et al, 2016;NICE Interventional Procedure Guidance [IPG347], 2010;Peliowski-Davidovich et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…La contención sanguínea y de oxígeno en el momento del nacimiento es capaz de acarrear daños en las células del sistema nervioso central, incluso la muerte celular. Segundo, cuando se restaura el flujo sanguíneo en un cerebro lesionado se desencadenan diversos efectos colaterales, pudiendo dañar las células neurales o hasta llevar a la muerte cerebral (2)(3)(4). Según la Organización Mundial de la Salud (OMS), la asfixia perinatal (AP) está entre las tres principales causas de muerte entre los neonatos (5).…”
Section: Introductionunclassified
“…Según la Organización Mundial de la Salud (OMS), la asfixia perinatal (AP) está entre las tres principales causas de muerte entre los neonatos (5). Hasta el 25% de los recién nacidos y el 8% de las muertes de niños menores de 5 años están directamente asociadas a la AP (2). Cada año, de cada 1000 nacidos vivos, tres a cinco presentará AP en el momento del nacimiento, aumentando los riesgos de las secuelas neurológicas (3).…”
Section: Introductionunclassified